Pengujian Lignoselulosa Tandan Kosong Kelapa Sawit dengan Waktu Delignifikasi H2SO4 Menggunakan Uap Bertekanan - Hartari, Widia Rini; Delvitasari, Febrina; Maryanti, Maryanti; Undadraja, Bigi; Hasbullah, Fizzaria; Deksono, Giannis Aji (Jurnal Agro Industri Perkebunan, 2023)
Oil palm empty fruit bunches (EFB) are the most abundant solid waste from the palm oil industry and are underutilized, even though they have the potential to become industrial raw materials because they contain three fractions, namely cellulose, hemicellulose, and lignin. This research was carried out using the steam method using 1 molar sulfuric acid with concentrations of 6.4%, 7.6%, and 8.7%. The delignification temperature was measured at 120 oC and with different delignification times of 60 minutes, 90 minutes, and 120 minutes. The best treatment with 1 M H2SO4 concentration and heating time for hemicellulose was the treatment with 8.7% H2SO4 concentration and 90 minutes of heating time. The best treatment with 1 M H2SO4 concentration and heating temperature for cellulose was found to be 6.4% H2SO4 concentration with 90 minutes of heating time. The best treatment with a 1 M H2SO4 concentration and heating temperature for lignin was the 6.4% H2SO4 treatment with 90 minutes of heating time.